Advancements In Anti-Viral Strategies Against Nipah Virus - Thomas, Anju; Jeas John (Jurnal Vokasi Kesehatan, 2024)
Since its discovery in Malaysia during the epidemic of 1998, Nipah virus or NiV, member of paramyxoviridae family, has become one of the emerging potential threats to world health due to its uncontrolled rate of fatality and absence of specific therapies. The recent outbreaks in South and Southeast Asia have called for urgent international efforts to curb the virus. Since most infections with NiV bring about severe respiratory and neurological symptoms, treatment has relied on supportive care. There are no human vaccines available for distribution, though some preclinical trials and very limited human trial versions of vaccines are in development. This review article emphasizes on the recent advances in the therapeutic approaches and prevention measures of NiV. New treatment strategies like Defective Interfering Particles and RNA silencing, other than conventional treatments like antiviral drugs have also been discussed.